Walimatul 'ursy and Music According to Islamic Scholars: Case Study in East Aceh - Fauzaruddin (International Journal of Sharia Studies, 2023)
One of the things that is sunnah at a wedding is holding a Walimatul Ursy. This is due to the many problematic values ​​that arise from the existence of the Walimatul Ursy. Among them is broadcasting and motivating the wedding. But nowadays it is not uncommon for Walimatul Ursy to cause problems in society. This is not only due to the concept of the Walimatul Ursy event which is full of elements of grandeur, but also the presence of music in a series at the event which often destroys the main substance of the Walimatul Ursy event. In this article the author concludes that Walimatul Ursy and music are two things that are permissible as long as they do not conflict with beneficial values, but if it is the opposite then the law becomes haram.